The evolution and application of the medical evidence chain - Bai, Yanan; Wang, Wanying; Duan, Jiajia; Wang, Xue; Jiang, Mingjing; Ni, Han; Sun, Lu; Liu, Chuanxin; Li, Ding (Frontiers in Medicine, 2025)
IntroductionSince the advent of evidence-based medicine, the decision-making process in disease diagnosis and treatment has exhibited fundamental principles that align closely with the core tenets of evidence chain theory in the legal field. Based on this, this paper aims to explore the underlying logic and practical value of transferring evidence chain theory from law to medicine, focusing on its significance in enhancing the scientific rigor and standardization of clinical decision-making.MethodsThrough systematic retrieval of existing literature in the fields of jurisprudence and medicine, this paper reviewed the theoretical evolution and practical applications of the evidence chain in jurisprudence, outlined the grading criteria for medical evidence, and elaborated on the construction methods and application examples of the integrated evidence chain and toxicological evidence chain.ResultsThe mutual corroboration among evidence materials significantly enhances the reliability and validity of conclusions. The theory of evidence chains plays a pivotal role in evaluating drug efficacy, elucidating toxicological mechanisms, optimizing clinical pathways, and designing high-quality clinical trials.ConclusionThe interdisciplinary application of the evidence chain theory contributes to advancing the standardization and normalization of evidence-based medical practice, thereby enhancing the quality of clinical decision-making and public health management.